Linking Genetic Counseling Content to Short‐Term Outcomes in Individuals at Elevated Breast Cancer Risk. Issue 5 (28th March 2014) - Kelly, Kimberly M.; Ellington, Lee; Schoenberg, Nancy; Agarwal, Parul; Jackson, Thomas; Dickinson, Stephanie; Abraham, Jame; Paskett, Electra D.; Leventhal, Howard; Andrykowski, Michael
Abstract: Few studies have linked actual genetic counseling content to short‐term outcomes. Using the Self‐regulation Model, the impact of cognitive and affective content in genetic counseling on short‐term outcomes was studied in individuals at elevated risk of familial breast‐ovarian cancer. Surveys assessed dependent variables: distress, perceived risk, and 6 knowledge measures (Meaning of Positive Test; Meaning of Negative Test; Personal Behavior; Practitioner Knowledge; Mechanisms of Cancer Inheritance; Frequency of Inherited Cancer) measured at pre‐ and post‐counseling. Proportion of participant cognitive and affective and counselor cognitive and affective content during sessions (using LIWC software) were predictors in regressions. Knowledge increased for 5 measures and decreased for Personal Behavior, Distress and Perceived Risk. Controlling for age and education, results were significant/marginally significant for three measures. More counselor content was associated with decreases in knowledge of Personal Behavior. More participant and less counselor affective content was associated with gains in Practitioner Knowledge. More counselor cognitive, and interaction of counselor cognitive and affective content, were associated with higher perceived risk. Genetic counselors dominate the content of counseling sessions. Therefore, their content is tied more closely to short term outcomes than participant content. A lack of patient communication in sessions may pose problems for understanding of complex concepts.